AB0334 Cardiac Echocardiography Findings of Patients with Rheumatoid Arthritis. (9th June 2015) - Yazici, A.; Cosan, F.; Yilmazer, B.; Cefle, A.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease which is found to cause the risk of cardiovascular diseases (1, 2). Objectives: In the present study, we aim to identify changes that are present in Echocardiograms of patients with RA. Methods: By analyzing the records of follow-up patients with RA in the clinics of Rheumatology in Kocaeli Faculty of Medicine, 200 patients with Echocardiograms (Male/ Female: 155/45, age range: 57.12±12.08 year, average duration of disease: 108.57±115.99 month) were examined. Results of Echocardiography were analyzed with regard to systolic and diastolic functions, problems with valves, and internal chamber size quantification. Results: It was found that of all patients 67.2% had positive RF and %58.4 had positive antiCCP, and 40% (80) of patients had other accompanying diseases. Of these 35.5% (71) had hypertension; 5% (10) had ischemic heart disease, and 14.1% (28) had diabetes. When the findings of Echocardiography were examined, 12 patients (6%) were diagnosed with systolic dysfunction, 9 (4.5%) patients were diagnosed with pericardial infusion, 17 (8.5%) patients were diagnosed with valvular dysfunction, and 128 (68.1%) patients were diagnosed with diastolic dysfunction. There was spontaneous echo contrast (SEC) in 2 patients with heart valve prosthesis. 41 (20, 5%) patients had pulmonary hypertension, and 184 (92%) had valve regurgitation, and only 14% of patients had medium and serious regurgitations (17 patients with mitral regurgitation, 15 patients with tricuspid, 10 patients with aortic and only 1 patient with pulmonary valve were identified). When left ventricular mass is calculated, 131 (65.5%) patients had an increase in hypertrophy; 33.5% of patients were affected by hypertrophy in left atrium and 11% in the right ventricular area. When findings were compared by taking accompanying diseases, sex and age (57.5% were above 55) into consideration, increase in left ventricular mass, left atrium hypertrophy and diastolic dysfunction were observed in patients over 55 age with accompanying diseases and pulmonary hypertension was identified more frequently in patients over 55 age. Conclusions: Due to increase in the risk of cardiovascular disease and accompanying other diseases various Echocardiography findings can be identified in many patients. References: van Breukelen-van der Stoep DF, Klop B, van Zeben D, Hazes JM, Castro Cabezas M.Cardiovascular risk in rheumatoid arthritis: how to lower the risk? Atherosclerosis. 2013 Nov;231(1):163-72. doi: 10.1016/j.atherosclerosis.2013.09.006 Barbhaiya M, Solomon DHRheumatoid arthritis and cardiovascular disease: an update on treatment issues. Curr Opin Rheumatol. 2013 May;25(3):317-24. Disclosure of Interest: None declared